The influence of non-native language proficiency on speech perception performance - Kilman, Lisa; Zekveld, Adriana; Hällgren, Mathias; Rönnberg, Jerker (Frontiers in Psychology, 2014)
The present study examined to what extent proficiency in a non-native language influences speech perception in noise. We explored how English proficiency affected native (Swedish) and non-native (English) speech perception in four speech reception threshold (SRT) conditions including two energetic (stationary, fluctuating noise) and two informational (two-talker babble Swedish, two-talker babble English) maskers. Twenty-three normal-hearing native Swedish listeners participated, age between 28 and 64 years. The participants also performed standardized tests in English proficiency, non-verbal reasoning and working memory capacity. Our approach with focus on proficiency and the assessment of external as well as internal, listener-related factors allowed us to examine which variables explained intra-and interindividual differences in native and non-native speech perception performance. The main result was that in the non-native target, the level of English proficiency is a decisive factor for speech intelligibility in noise. High English proficiency improved performance in all four conditions when target language was English. The informational maskers were interfering more with perception than energetic maskers, specifically in the non-native language. The study also confirmed that the SRT's were better when target language was native compared to non-native.